The Interaction between China, Japan, and Korea in the Export Market - JUNG, Kyu-Chul (Korea Development Institute, 2016)
This paper analyzes changes in the export potential and competitiveness of China, Japan, and Korea. The analysis of Japan’s export market share reveals that in sectors where Korea’s potential was strong in the early 1990s, Japan’s market share diminished. This suggests the possibility that Korea was catching up with Japan, eating into Japan’s market share. The same analysis of Korea’s export market share in the 2000s shows, for items in which China’s export potential was high, Korea’s market share has declined comparatively since 2010, with the tendency growing much larger. China’s export potential continues to expand in markets for Korea’s key export products, making it difficult to rule out the possibility that Korea’s competitiveness in key export products will be hindered, driven by the catching up of China. To respond to these challenges, it is important for Korea continuously to foster and enhance creative and core capabilities that latecomers will not easily be able to emulate.